Cost-effectiveness analysis of MRI, CE-CT and 18F-FDG PET/CT for detecting colorectal liver metastases eligible for hepatic resection - Schnitzer, Moritz L.; von Münchhausen, Niklas; Biechele, Gloria; Runtemund, Jasmin; Grawe, Freba; Geyer, Thomas; Kaiser, Clemens G.; Haag, Florian; Rübenthaler, Johannes; Froelich, Matthias F. (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is a serious challenge for the health system. In 2022 CRC represented 8% of cancer diagnoses in the United States. 30% of patients already show metastases at the initial tumor staging. The majority of these metastases are sited in the liver. According to their extension and the status of the tumor colorectal liver metastases can be treated in several ways, with hepatic resection being the gold-standard. Contrast-enhanced computed tomography (CE-CT), positron emission tomography/ computed tomography (PET/CT) and magnetic resonance imaging (MRI) can be used for evaluation of resectability of these liver metastases. The aim of this study is to assess the most economic imaging modality for detecting liver metastases eligible for hepatic resection by analyzing their cost-effectiveness.In our study, a Markov state transition model was built to calculate the quality-adjusted life years (QALYs) and overall costs for each diagnostic strategy in accord with the stated input values obtained from scientific research. Further, probabilistic sensitivity analyses by means of Monte Carlo simulations were performed to consider possible model uncertainties. For evaluation of the costeffectiveness on an economic threshold, the Willingness-to-pay (WTP) was set at $ 100,000. The applied values and the calculated results are based on the U.S. healthcare system. of $ 42,874.02 and 8.47 QALYs, whereas MRI led to $ 40,863.65 and 8.50 QALYs. PET/CT resulted in overall costs of $ 43,216.74 and 8.48 QALYs. Therefore, MRI was determined to be the dominant strategy in the model. According to the performed sensitivity analyses, MRI remained cost-effective over a wide range of WTPs.In conclusion, according to our analysis, MRI is the dominant strategy for detecting hepatic metastases eligible for hepatic resection in colorectal cancer.